Transformation of E. coli modified gdha gene into Nicotiana tabacum - Hang, Pham Thi; Linh, Nguyen Thuy; Viet, Le Bac; Lien, Nguyen Thi Kim; Hien, Le Thi Thu; Hue, Huynh Thi Thu (Academia Journal of Biology, 2019)
The bacterial gdhA gene encodes NADH-GDH enzyme. The gdhA-transgenic tobacco plants exhibited high growth performance and enhanced herbicide resistance as well as drought tolerance. In addition, the gdhA gene when expressed in maize plants could increase productivity because of improving stress tolerance. In this study, we isolated and analyzed a gdhA gene from the E. coli strain JM109. Then, the E.coli derived-gdhA sequence was modified by using OptimumGene™ software for plant compatibility. The optimized gdhA gene was inserted into an expression cassette containing the CaMV 35S promoter and the 35S terminator of the pRTRA7/3 vector. The 35S::gdhA::35S construct was ligated into the plant expression plasmid pCAMBIA1300 which then introduced into the A. tumefaciens strain EHA105. In order to examine the expression of the gdhA gene, we created gdhA-transgenic plants via Agrobacterium-mediated transformation into N. tabacum K326. The PCR analysis showed that two out of 20 plants were positive to the presence of the gdhA gene. The RT-PCR experiment also revealed that gdhA was expressed in transcriptional level. These results suggested that the gdhA expression construction can be transformed into other crops such as maize.